From Inflammation to Prostate Cancer: The Role of Inflammasomes. (27th June 2016) - Karan, Dev; Dubey, Seema
Abstract : Inflammation-associated studies entice specific attention due to inflammation's role in multiple stages of prostate cancer development. However, mechanistic regulation of inflammation inciting prostate cancer remains largely uncharacterized. A focused class of inflammatory regulators known as inflammasomes has recently gained attention in cancer development. Inflammasomes are a multiprotein complex that drives a cascade of proinflammatory cytokines regulating various cellular activities. Inflammasomes activation is linked with infection, stress, or danger signals, which are common events within the prostate gland. In this study, we review the potential of inflammasomes in understanding the role of inflammation in prostate cancer.